Supporting Student Transduction of Meanings Across Modes in Primary School Astronomy - Tytler, Russell; Prain, Vaughan (Frontiers in Communication, 2022)
The multimodal nature of knowledge development (Gooding, 2004; Latour, 1990) and learning in science (Lemke, 1990) is now increasingly recognized. While researchers have focused on identifying how different representational modes afford meaning-making, the question of how students are guided to link, confirm and expand similar and different meanings across modes, called ‘transduction’ (Kress & van Leeuwen, 2006, p. 39), has been less explored. This transduction process is fundamental to students realising, aligning, generating and coordinating representations to learn concepts and processes in science (Kozma & Russell, 2005; Prain & Tytler, 2021; Volkwyn, 2019). In this paper we focus on a learning sequence in primary school astronomy designed around representational work to explore the teacher’s key role in supporting student transduction. In the Interdisciplinary Mathematics and Science (IMS) project we developed a pedagogy with stages of orienting, posing representational challenges, evaluating and building consensus, and applying and extending conceptual understanding. We use micro-ethnographic analysis of the teacher’s strategic framing and interactions with students and their artefacts to: 1) explore the fundamental role, the nature of, and challenges associated with transduction as students engage with material and representational work, and 2) the role of the teacher in anticipating challenges for students in integrating meanings across multiple, multimodal representations of astronomy phenomena.